Teaching English as a Lingua Franca: EFL Teachers' Perception - Julwinda Julwinda; Iwan Setiawan; Bibit Suhatmady (Globish: An English-Indonesian Journal for English, Education, and Culture, 2026)
The importance of English as a Lingua Franca (ELF) had increased due to the growing demand for English competence worldwide, especially in Southeast Asia. This research explored EFL teachers’ perceptions regarding the teaching of English as a Lingua Franca and how their understanding of ELF influenced classroom practices. A qualitative survey design was employed to gather data from 15 EFL teachers in Indonesia and Thailand through questionnaires and interviews. The results showed that although the majority of teachers were aware of English as a Lingua Franca (ELF), they continued to teach primarily British English. They wished to assist students with language and cultural skills since they recognized that English differed by culture. To support teaching English in a more inclusive and relevant way, it was important to increase to more ELF knowledge, improved training, and updated global communication curricula are all need for teachers to advance.